2014
DOI: 10.1124/jpet.114.220194
|View full text |Cite
|
Sign up to set email alerts
|

A UGT2B10 Splicing Polymorphism Common in African Populations May Greatly Increase Drug Exposure

Abstract: RO5263397 [(S)-4-(3-fluoro-2-methyl-phenyl)-4,5-dihydro-oxazol-2-ylamine], a new compound that showed promising results in animal models of schizophrenia, is mainly metabolized in humans by N-glucuronidation. Enzyme studies, using the (then) available commercial uridine 59-diphosphate-glucuronosyltransferases (UGTs), suggested that UGT1A4 is responsible for its conjugation. In the first clinical trial, in which RO5263397 was administered orally to healthy human volunteers, a 136-fold above-average systemic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 36 publications
2
49
1
Order By: Relevance
“…The safety, tolerability, pharmacokinetics, and pharmacodynamics after oral administration of one of these molecules, RO5263397, a TAAR1 partial agonist that is well tolerated in rat and cynomolgus monkey toxicity studies, was determined in a singleascending dose, randomized, double-blind, placebocontrolled study in healthy male volunteers. Although the compound was found to be generally safe, a 136-fold above-average systemic exposure to the parent compound was found in one participant (Fowler et al, 2015). An additional two poor metabolizers were subsequently identified, and all three were of African origin.…”
Section: B Trace Amine-associated Receptormentioning
confidence: 95%
See 2 more Smart Citations
“…The safety, tolerability, pharmacokinetics, and pharmacodynamics after oral administration of one of these molecules, RO5263397, a TAAR1 partial agonist that is well tolerated in rat and cynomolgus monkey toxicity studies, was determined in a singleascending dose, randomized, double-blind, placebocontrolled study in healthy male volunteers. Although the compound was found to be generally safe, a 136-fold above-average systemic exposure to the parent compound was found in one participant (Fowler et al, 2015). An additional two poor metabolizers were subsequently identified, and all three were of African origin.…”
Section: B Trace Amine-associated Receptormentioning
confidence: 95%
“…Subsequent DNA database analyses revealed the UGT2B10 splice site mutation was highly frequent in individuals of African origin (45%), compared with only moderate frequency in Asians (8%) and an almost complete absence in Caucasians (,1%). A prospective study using hepatocytes from 20 individual African donors demonstrated a greater than 100-fold lower intrinsic clearance of RO5263397 in cells homozygous for the splice site variant allele (Fowler et al, 2015). Based on this unexpected finding in the phase I study, a novel chemical series of potent and selective TAAR1 agonists with improved pharmacokinetic properties will be required to allow further clinical development.…”
Section: B Trace Amine-associated Receptormentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the reported K i for desloratadine (;1 mM), Kazmi et al (2015b) predicted a 2.2-fold increase in the AUC ratio for UGT2B10 substrates, which is similar to that proposed in this work for amitriptyline, doxepin, and mianserin. It is noteworthy that few compounds appear to be solely metabolized by UGT2B10, although the clearance of the experimental antipsychotic agent RO5263397 appears to be mediated largely by UGT2B10 (Fowler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although initially considered an orphan enzyme, more recent studies have shown that UGT2B10, like UGT1A4, catalyzes the N-glucuronidation of a number of xenobiotics that incorporate an aliphatic tertiary amine or aromatic N-heterocyclic group (Kaivosaari et al, 2011). Known substrates are nicotine and its oxidation product cotinine (Chen et al, 2007;Kaivosaari et al, 2007); desloratadine (Kazmi et al, 2015a); medetomidine (Kaivosaari et al, 2008); the tricyclic antidepressants (TCAs) amitriptyline, clomipramine, imipramine, and trimipramine (Chen et al, 2007;Zhou et al, 2010;Kato et al, 2013); several tobacco-specific nitrosamines (Chen et al, 2008); RO5263397 (Fowler et al, 2015); and miscellaneous drugs that include diphenhydramine, ketoconazole, ketotifen, midazolam, olanzapine, pizotifen, and tamoxifen (Erickson-Ridout et al, 2011;Kato et al, 2013). Consistent with the known selectivity of UGT1A4 for N-glucuronidation (Kubota et al, 2007), most, if not all, UGT2B10 substrates are additionally glucuronidated by UGT1A4 and biphasic kinetics are frequently observed when human liver microsomes (HLM) are used as the enzyme source (Kaivosaari et al, 2011;Kato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%